2012
DOI: 10.1111/j.1461-0248.2011.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenology drives mutualistic network structure and diversity

Abstract: Several network properties have been identified as determinants of the stability and complexity of mutualistic networks. However, it is unclear which mechanisms give rise to these network properties. Phenology seems important, because it shapes the topology of mutualistic networks, but its effects on the dynamics of mutualistic networks have scarcely been studied. Here, we study these effects with a general dynamical model of mutualistic and competitive interactions where the interaction strength depends on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 52 publications
7
136
0
1
Order By: Relevance
“…Greater phenological overlap in birds and plants led to greater number of interactions between pairs of species. The importance of phenology in explaining pairwise interactions has also been found in other studies, but was still found to be a poor predictor of observed interactions in some cases (Encinas-Viso, Revilla & Etienne, 2012; Olito & Fox, 2015). …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Greater phenological overlap in birds and plants led to greater number of interactions between pairs of species. The importance of phenology in explaining pairwise interactions has also been found in other studies, but was still found to be a poor predictor of observed interactions in some cases (Encinas-Viso, Revilla & Etienne, 2012; Olito & Fox, 2015). …”
Section: Discussionsupporting
confidence: 74%
“…Species extinction can be preceded by the extinction of species interactions, so this study contributes to show how network theory can help to explain the web of life in an ecosystem (Bascompte & Jordano, 2014). In recent years, new analytical approaches have facilitated asking questions about the processes that drive network properties (Vazquez, Chacoff & Cagnolo, 2009; Encinas-Viso, Revilla & Etienne, 2012; Winfree et al, 2014; Vizentin-Bugoni, Maruyama & Sazima, 2014; Olito & Fox, 2015). Two main hypotheses—neutrality and biological constraints—have emerged in these network studies.…”
Section: Introductionmentioning
confidence: 99%
“…3). A change in coflowering represents altered interaction potential (27), which can affect various ecological processes (19). Increased coflowering between plant species can exacerbate direct interspecific competition for abiotic resources (28) and can affect plant reproductive success indirectly via competition for or facilitation of pollination (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…Fruiting phenology is an important constraint of plantdisperser interactions [53], although knowledge regarding fruiting phenology of most Galápagos plants is very limited. The pattern described here of sequential ripening of native fruits in the Galápagos is compatible with an inter-specific strategy to avoid satiation of dispersers, in line with what has been suggested for asynchronous fruit ripening within conspecific plants [54].…”
Section: (A) the Role Of Different Vertebrates As Seed Dispersersmentioning
confidence: 99%